Regular exercise in adolescents with ACE gene polymorphism helps preventing cardiovascular risk factors - Nivaldo de Jesus Silva Soares Junior; Carlan Senna; Carlos Alberto Alves Dias-Filho; Bruno Rodrigues; Maria Claudia Irigoyen; Danielle da Silva Dias; Vinícius Santos Mendes; Carlos José Moraes Dias; Sally Cristina Moutinho Monteiro; Cristiano Teixeira Mostarda (ABCS Health Sciences)
Introduction: Polymorphisms can influence the expression and production of regulatory components in the endocrine system. These include the renin-angiotensin-aldosterone system (RAAS), which plays, along with other environmental factors, a fundamental role in the pathogenesis of essential arterial hypertension in both adults and adolescents. Objective: To analyze the influence of the level of physical activity and the polymorphism in the ACE gene on cardiac autonomic modulation and the chance of cardiovascular risk in adolescents. Methods: 136 adolescents were divided into active (AG) and sedentary (SG) groups. The genotypic frequencies in SG group are DD (38), DI (12) and II (10); and AG group are DD (38), DI (15) and II (23). Blood pressure, body composition, physical activity level, and sexual maturation were assessed to characterize the groups. Afterward, an electrocardiogram was performed to analyze heart rate variability and oral mucosal cells were collected for the genotypic of angiotensin-converting enzyme. Results: The AG presented lower systolic blood pressure and sympathetic modulation when compared to the SG DD. Additionally, the odds ratio for the cardiovascular events was increased in the SG DD compared with that in AG with DD allele (AG DD) adolescents, as verified for the autonomic variables LF%, HF%, LF/HF, and SBP. Conclusion: Regular physical activity in adolescents can contribute to the maintenance of blood pressure levels, preventing autonomic imbalance and cardiovascular risk factors in adolescents with ACE gene polymorphism.